A Number of Conflicts at Route Intersections - Rectangular Model - Havel, Karel; Balint, Vojtech; Novak, Andrej (Communications - Scientific letters of the University of Zilina, 2017)
A conflict is an infringement of minimum separation between at least two aircraft. Air traffic controllers build a protected area in front of an aircraft; its shapes and dimensions depend on the speed of an aircraft and on the minimum separation. The protected zone in this mathematical model is the horizontal rectangular zone. If an aircraft is inside this protected zone, a conflict occurs. The model is based on these assumptions: aircraft fly in level straight line routes; only an infringement of the lateral separation is considered; deviations are excluded; aircraft at the same flight level fly at the same average speed; aircraft fly towards an intersection and change direction after the intersection. Hence, conflicts mainly occur owing to the loss of minimum separation between aircraft flying at the same flight level. The calculation of average number of potential conflicts is designed for a long time interval; hence, aircraft velocity deviations are negligible. The mathematical model in this paper is intended to compare different alternative intersection configurations of air traffic service routes. The comparison is based on the following results: an average number of potential conflicts per hour at route intersections, index of conflict intensity, and intersection capacity.